Barriers and facilitators to health care access for children in a low-income are in Cape Town - Profitt, Luke (Department of Public Health and Family Medicine, 2023)
Background In Cape Town the under-5 mortality rate has plateaued to 20 per 1000 live births. The southern subdistrict has the largest paediatric population in Metro West and accounts for 31% of deaths in Metro West. Across the metropole 60% of child deaths are out of hospital. We investigated barriers to accessing health care for children in the False Bay Hospital drainage area. Methods Quantitative and qualitative methods were used: community survey (n=62), qualitative interviews (n=11) with caregivers of children who presented critically ill or deceased (January 2017 - Dec 2020) and a modified nominal group meeting of community based and clinical services managers to identify and achieve consensus on solutions. Results Community members (74%) experienced barriers in accessing care and only 60% knew the correct emergency contact numbers. Knowledge of basic home care for common conditions was limited. Interview themes showed barriers of affordability, acceptability, access, as well as household and facility factors. The nominal group technique suggested that improvement in community-based services, transport access and lengthening service hours would alleviate some of the challenges in accessing care. Conclusions The barriers to accessing care seem insurmountable to those who encounter them, yet solutions and community assets do exist. The optimal utilization of services and community assets have the potential to improve access to care with resultant decreased out-of-hospital deaths and improvement of the under-5 mortality rate. A well-coordinated Community Orientated Primary Care (COPC) program with intersectoral collaboration and government commitment needs to be implemented.